Poetic walls in Al-Hamraa palace -Analytical study-: Poetic walls in Al-Hamraa palace -Analytical study- (Journal of the College of Education for Women, 2019)
Abstract:Al-Hamraa palace considers one of the most important urban tracesthat the Arab left behind in Andalus .Muhammed bin Al—Ahmer put its fiststones then it was finished later by his thrown hirer .The poems of (ibn-Zumrek)were graved on the palaces doors ,halls, and lion cages with all theproud and dignity those poems contain.This search identifies this palace first, then studies the contents of thepoems on Walls ,then the Urban features, and description of the palace sites,buildings materials ,pillars ,decorations, and the geometricalVocabularies in the poems such as spaces , direction ,distance ,andheight.Then the search describes the technical engineering of wordscoordination, the meeting , comprehension, division and varieties in the colors, pictures, methods and structures .The symbolic , opposite ,motional pictures were discussed also, it wasfound that the diagnostic metaphor is the most famous one because thispalace was supposed to live in the memory of the reader in spite of age andhard times .